Dental caries experience and oral health behaviour; A survey of a Nigerian rural adult population. - Nnawuihe, Ukachi Chiwendu; Sofola, Oyinkansola O; Okeigbemen, Sunny Ajimen (International Association for Dental Research (Nigeria Division), 2022)
Abstract Objectives: Dental caries is one of the most common chronic oral diseases. Its burden in Nigerian rural communities is relatively high because it is largely untreated. There is scanty data on dental caries experience in Nigerian rural adult communities. This study seeks to increase the pool of data on dental caries and its determinants in this population. Methods: Data on socio-demographic characteristics and oral health behaviour were obtained using questionnaires. World Health Organisation Oral Health Survey caries diagnostic criterion was used for caries assessment. Data was analysed at 95% confidence interval with test for significance set at (p<0.05). Results: Study participants were 490. The age ranged from 18 to 92 years with a mean age (± SD) of 36.1 ± 15.8. Majority had poor oral health behaviour. Coronal and root caries prevalence were 47.1% and 8.4% respectively. Females have a higher prevalence of dental caries (50.0%) than males (44.6%). The mean DMFT and Significant caries index was 1.17 ± 1.93 and 3.03 ± 2.37 respectively. The decayed teeth component of the DMFT contributed 96.5% of the total DMFT value while the filled teeth component made no contribution. Elderly (≤ 65 years), study participants with non-formal education and who reported relatively high refined sugar consumption were significantly associated with higher caries experience. Conclusion: Caries prevalence was relatively high with inequalities in caries experience among the various socio-demographic strata of the study group. Multi-sectorial interventions to improve oral health behaviour, adequacy and accessibility of existing dental services are needed in this study population.